2010
DOI: 10.1128/jcm.00670-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Methicillin-Resistant Staphylococcus aureus (MRSA) in Specimens from Various Body Sites: Performance Characteristics of the BD GeneOhm MRSA Assay, the Xpert MRSA Assay, and Broth-Enriched Culture in an Area with a Low Prevalence of MRSA Infections

Abstract: Universal surveillance upon patient admission is important in reducing the transmission of methicillinresistant Staphylococcus aureus (MRSA) and associated disease in hospitals. High costs for the health care system in conjunction with MRSA have promoted the development of rapid screening methods to detect MRSA carriers. This study compared two real-time PCR methods, the BD GeneOhm MRSA assay (BDGO) and the Xpert MRSA assay, with broth-enriched culture to define their performance characteristics and rapidity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…An active MRSA surveillance program that uses a laboratory test with 98% sensitivity and with a reporting time of Յ15 h can capture 85% of potential inpatient MRSA isolation days, leading to a significant (Ͼ70%) reduction in MRSA infection (28). For these reasons, tremendous amounts of effort and resources have been focused on the development of several new molecular-based rapid screening tests for MRSA (12)(13)(14)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An active MRSA surveillance program that uses a laboratory test with 98% sensitivity and with a reporting time of Յ15 h can capture 85% of potential inpatient MRSA isolation days, leading to a significant (Ͼ70%) reduction in MRSA infection (28). For these reasons, tremendous amounts of effort and resources have been focused on the development of several new molecular-based rapid screening tests for MRSA (12)(13)(14)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA screening using molecular amplification methods provides faster results than culture and has been demonstrated to be more sensitive (11)(12)(13)(14)(15). However, most of the molecular commercially available rapid tests are based on the detection of a sequence indicating the integration of the staphylococcal cassette chromosome mec element (SCCmec) within the chromosome and do not specifically target the methicillin resistance gene mecA (16).…”
mentioning
confidence: 99%
“…Whether disease caused by mecA LGA251 S. aureus is identical to that caused by conventional MRSA is not clear without evidence from formal epidemiological and virulence studies. The Xpert MRSA nasal assay and the MRSA/SA ELITe MGB kit were chosen for this study because both have good classical performance parameters, such as sensitivity, specificity, PPV, and NPV, and the results are rapidly available with both kits (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, livestock-associated MRSA carrying variant mecC genes further complicated the epidemiology of MRSA by increasing its molecular diversity (5). Microbiology laboratories usually define MRSA phenotypically, but the underlying genetic structures responsible for this phenotype are constantly changing (6)(7)(8), and the molecular assays designed several years back are not necessarily relevant to the epidemiology observed today (9)(10)(11). A recent comparison of culture and a commercial molecular assay performed in a high-prevalence environment showed the molecular assay to be slightly less sensitive than enriched culture using ChromID MRSA agar but also showed that the results were not significantly different, although the molecular assay yielded results in hours instead of days (12).…”
mentioning
confidence: 99%